Token Economy (Hadiah) untuk Penyelesaian Tugas dalam Layanan Penguasaan Konten - Yeni Satroma Dewi; Herman Nirwana; Neviyarni S (Jurnal Konseling dan Pendidikan, 2015)
To learn so far a bout token economy in the completion students task at V grade in SD N 16 Sungayang. This research includes qualitative research with this type of case studies. The invent of this research show that applying token economy has a great influence to ward students behave in the completion mathematic task in the class. The implication application of token economy can support the implementation of service delivery mastery of content in completing learning tasks and giving other Guidance. A counselor can collaborate with some of the teachers to improve students behavior and students quality. It is hoped to the next beseecher to apply token economy in the different field to get more view.